الدلالات النفسية في رواية الزمن المستحيل لوفاء عبد الرزاق دراسة نفسية - رضواني, صبرين, عبادي سعيدة (University of El-oued, 2021)
يأخح البعج الشفدي دلالات متشػعة , تختمف باختلبؼ شكل الإعاقة عمى الذخرية كحزػرىا في الشز السدخكد, حيث تكذف ركاية الدمغ السدتحيل للؤديبة كفاء عبج الخازؽ عغ الؿيسة الجسالية, كيسكغ استجلبء أىسية الدخد بالتجقيق في البشية الدخدية لمشز, بػصفو عسلب متشاميا بباخعة. كإف لمحزػر السكاني تجمياتو عمى أشكاؿ الذخرشة, بحيث يطيخ اربط الجلالة الشفدية السذتخكة في الخكاية بيغ الذخرية السعاقة كشبيعة السكاف الحؼ يجاعب كجػدىا, كذلظ لخرػصية السكاف كدكره . في الشديج الخكائي ّالفعاؿ Summary: The psychological dimension takes on various connotations, differing according to the form of disability on the personality and its presence in the text listed, where the novel “The Impossible Time” by the writer Wafaa Abdel Razzaq reveals the aesthetic value, and the importance of narration can be clarified by examining the narrative structure of the text, as it is a brilliantly growing work. The spatial presence has its manifestations in the forms of personalization, so that the common psychological significance link appears in the novel between the disabled character and the nature of the place that flirts with its presence, due to the specificity of the place and its active role in the narrative fabric
Keywords: الشخصية و البنية السردية